1994
DOI: 10.2307/3869894
|View full text |Cite
|
Sign up to set email alerts
|

Light Modulation of Ferredoxin mRNA Abundance Requires an Open Reading Frame

Abstract: Ferredoxin I (Fed-l) mRNA abundance is modulated by an Interna1 light regulatory element that includes sequences both L'and 3'of the translational initiation site. To test the hypothesis that the light response mediated by this element might be coupled to translation, we transformed tobacco plants with gene constructs blocked in translational initiation or elon-gation. Here, we report that such mutations abollsh the light response ln vivo. A nonsense mutation could be rescued by restorlng the open reading fram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

1998
1998
1998
1998

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…Previously, we showed that changes in Fed-1 mRNA abundance are correlated with the ability of the mRNA to be translated (2). The data presented here support the suggestion that Fed-1 is preferentially degraded when it is not associated with polyribosomes.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Previously, we showed that changes in Fed-1 mRNA abundance are correlated with the ability of the mRNA to be translated (2). The data presented here support the suggestion that Fed-1 is preferentially degraded when it is not associated with polyribosomes.…”
Section: Discussionsupporting
confidence: 88%
“…Mutation of the Fed-1 initiation codon to either a missense or nonsense codon abolishes light regulation of the mRNA (2). Similarly, mutation of the surrounding translational initiation context also compromises light regulation of the Fed-1 mRNA (7).…”
mentioning
confidence: 99%